Classroom Teachers' Problems and Strategies in Implementing the Merdeka Curriculum: Permasalahan dan Strategi Guru Kelas dalam Implementasi Kurikulum Merdeka - Mahardika Darmawan Kusuma Wardana (Academia Open, 2024)
General Background: The introduction of the Kurikulum Merdeka in Indonesia aims to enhance student competence and character by offering more flexible and student-centered learning approaches. Specific Background: While it promises a more inclusive and modern educational environment, the implementation poses challenges for teachers adapting to this new paradigm. Knowledge Gap: Previous studies have focused on policy impacts and student outcomes, but there is limited research on the specific difficulties faced by classroom teachers during implementation. Aims: This study seeks to identify the challenges teachers encounter with the Kurikulum Merdeka and the strategies they employ to overcome these challenges. Results: Analysis of literature reveals several key issues: teachers' inadequate understanding of the curriculum's concepts, difficulty in designing student-centered learning, lack of resources, and challenges with competency-based assessments. Strategies to address these include ongoing professional development, fostering professional learning communities, leveraging technology, and developing authentic assessments. Novelty: This research contributes to the literature by focusing on teachers' perspectives, providing insights into practical challenges and solutions in implementing the Kurikulum Merdeka. Implications: Findings can guide the design of teacher training programs and inform educational policymakers to support effective curriculum implementation, ultimately benefiting Indonesia's educational landscape by preparing students for the challenges of the 21st century. Highlights: Teacher Training: Continuous professional development is crucial for teachers to effectively implement the Kurikulum Merdeka. Resource Limitations: Adequate access to educational resources and facilities is necessary for supporting innovative teaching methods. Assessment Challenges: Developing and utilizing authentic assessments can enhance the evaluation of student competencies. Keywords: Kurikulum Merdeka, Student-Centered Learning, Teacher Challenges, Competency-Based Assessment, Educational Innovation